A Systematic Customer Oriented Approach based on Hesitant Fuzzy AHP for Performance Assessments of Service Departments - ŞENVAR, ÖZLEM (SPRINGER INTERNATIONAL PUBLISHING AG, 2018)
Customer orientation is a business strategy in the lean business model that requires management and employees to focus on the changing demands and requirements of the customers. Improved business performance can be enhanced by. customer orientation. In this chapter, a systematic approach based on hesitant fuzzy AHP is proposed to deal with incomplete information due to the ambiguity to solve complex customer oriented multi criteria decision making problem of performance assessments of service departments.
Keywords: Customer orientation; Hesitant Fuzzy AHP; Hesitant Fuzzy Sets; MULTICRITERIA DECISION-MAKING; ORIENTATION